The effect of humility on emotional and social competencies: The mediating role of judgment - Rosa Hendijani (Taylor & Francis Group, 2019)
Leadership competencies are important contributing factors of successful performance among leaders. As theory suggests, humility can have a significant effect on building emotional and social competencies. In this study, we examine the effect of humility on competencies both directly and indirectly, through its effect on judgment. We designed and conducted a self-reported survey to measure humility, judgment, and emotional and social competencies among 165 management students. The results of our study showed that humility had a significant positive effect on emotional and social competencies, including self-awareness, self-management, social awareness, and relationship management. In addition, judgment had a significant mediating role on the relationship between humility and competencies. These results provide support for the important role of humility on personal learning and development as was previously discussed in the literature. Considering its important role, strategies have been recommended in the discussion section to improve humility both at personal and organizational levels.